Democratic Governance and Participatory Budgeting: A Theoretical Discourse of the Nigerian Experience (Global Journal of Human-Social Science, 2012)
This paper examines the issue of Democratic governance and participatory budgeting in the context of their relevance challenges and implications for the public sector finances and or public spending and the masses in Nigeria It specifically focuses on the Nigerian experience situation The necessary interconnectedness among these concepts was identified and examined vis- -vis the implications of such affinities for the people s ability to understand where the ultimate powers over public policies in these respects abound
Keywords: Democratic governance; participatory budgeting